2012
DOI: 10.1002/art.34348
|View full text |Cite
|
Sign up to set email alerts
|

Rates of malignancy associated with juvenile idiopathic arthritis and its treatment

Abstract: Objective To determine relative rates of incident malignancy among children with juvenile idiopathic arthritis (JIA) with respect to treatment compared to children without JIA Methods Using national U.S. Medicaid data from 2000 through 2005, we identified cohorts of children with JIA and without JIA using physician diagnosis codes and dispensed medication prescriptions. Study follow-up began after a 6 month lag period to exclude prevalent and misdiagnosed malignancies. Treatment with methotrexate and TNF inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 155 publications
(74 citation statements)
references
References 65 publications
4
65
3
1
Order By: Relevance
“…Most children are exposed to multiple agents over time, such that pinpointing adverse event association with a single product is problematic. Lastly, as previously described, having rheumatic diseases may predispose children to increased risks for adverse events irrespective of therapy, 6,24 although the magnitude of this baseline risk is poorly quantified.…”
Section: Current State Of Safety Research In Pediatric Rheumatologymentioning
confidence: 90%
See 1 more Smart Citation
“…Most children are exposed to multiple agents over time, such that pinpointing adverse event association with a single product is problematic. Lastly, as previously described, having rheumatic diseases may predispose children to increased risks for adverse events irrespective of therapy, 6,24 although the magnitude of this baseline risk is poorly quantified.…”
Section: Current State Of Safety Research In Pediatric Rheumatologymentioning
confidence: 90%
“…Subsequent studies have demonstrated an increased baseline rate of malignancy among all children who have juvenile idiopathic arthritis (JIA) compared with the general population even without biologic exposure. [6][7][8]9 However, other studies have not revealed increased malignancy risk in JIA, highlighting the need for more robust longer-term studies with active comparators rather than historical controls. 10 Other events of interest in children treated with immunomodulatory products include opportunistic infections, lupus or lupuslike illnesses, demyelinating diseases, pulmonary hypertension, inflammatory bowel disease, and uveitis.…”
Section: Current State Of Safety Research In Pediatric Rheumatologymentioning
confidence: 99%
“…The authors found an increased incidence of malignancy among children with JIA compared with unaffected children (SIR 4.4; 95 % CI 1.8-9.0), but, when patients were divided according to exposure to biologics or methotrexate, treatment did not appear to be significantly associated with the development of malignancy [25].…”
Section: Malignanciesmentioning
confidence: 94%
“…Indeed, medications that are used to treat JIA suppress the immune system, potentially increasing the risk of selected malignancies, but a disease-related increased risk of malignancies among children has also been suggested [25].…”
Section: Malignanciesmentioning
confidence: 99%
“…In regard to the safety of biologics, there have been increasing data on long-term outcomes, with reassuring findings reported in several studies [5,[10][11][12][13]. However, the safety and efficacy of higher dose biologics for pediatric patients with a diversity of diseases have not been reported.…”
Section: Introductionmentioning
confidence: 99%